Semantic Preference on Journal Articles: Corpus-Based Study of Adjectives in English - Meira Purnama Yanti, Ni Putu (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
The first part of this study is to investigate the semantic preference of the most frequent adjectives in journal articles through corpus-based analysis of the articles published in five journals in the three corpora (Humanities, Health Sciences, and Social Politics). The corpus-based analysis was carried out on the corpus to identify the most frequent adjectives that co-occurred in the five journals. By observing the concordance of the adjectives and analyzing the words they associated with, the semantic preferences of each adjective were determined. Then, the second part of this study aims to describe the differences and similarities between the three corpus (humanities, health sciences, and social politics) concerning the use of adjectives on journal articles from both areas. The results show that there are only three adjectives that collocate with the nouns, namely cognitive, different, and high. The use of the adjectives, especially “different” and “high” show the similarities and differences in the three corpora, meanwhile the adjective “cognitive” only exists in the Humanities corpus, thus it cannot be found the similarities and differences with other two corpora. In the corpus of Humanities and Health Sciences, the adjective “different” is used in the results and discussion section of the journal articles. Meanwhile, the differences are in the domain of each discipline. In the Health Sciences and Social Politics corpus, the similarities of the adjective “high” are in terms of indicating the measurement and quantification. While the differences are the use of the adjective in the part of journal articles of both corpora. Meanwhile, the differences are in the domain of each discipline. In the Health Sciences and Social Politics corpus, the similarities of the adjective “high” are in terms of indicating the measurement and quantification. While the differences are the use of the adjective in the part of journal articles of both corpora)